2022
DOI: 10.3390/ijms23137281
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Methylome Signature and Their Functional Roles in Colorectal Cancer Diagnosis, Prognosis, and Chemoresistance

Abstract: Colorectal cancer (CRC) is one of the leading causes of cancer-related deaths worldwide. Despite significant advances in the diagnostic services and patient care, several gaps remain to be addressed, from early detection, to identifying prognostic variables, effective treatment for the metastatic disease, and the implementation of tailored treatment strategies. MicroRNAs, the short non-coding RNA species, are deregulated in CRC and play a significant role in the occurrence and progression. Nevertheless, microR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…Despite the fact that miRNA biogenesis is a highly controlled process, miRNA dysregulation has been directly associated with tumorigenesis and multiple cancer types, including CRC [4]. The differential expression of miRNAs has also been correlated with the molecular profile of CRC, tumor size and location (left versus right colon), presence of microsatellite instability (MSI) and response to cancer therapy [5]. Furthermore, their role in cancer drug resistance/response has been widely studied in several malignancies, including CRC [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that miRNA biogenesis is a highly controlled process, miRNA dysregulation has been directly associated with tumorigenesis and multiple cancer types, including CRC [4]. The differential expression of miRNAs has also been correlated with the molecular profile of CRC, tumor size and location (left versus right colon), presence of microsatellite instability (MSI) and response to cancer therapy [5]. Furthermore, their role in cancer drug resistance/response has been widely studied in several malignancies, including CRC [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, biomarkers associated with the epigenome of tumors have gained more attention. Among these, microRNAs (miRNAs) are becoming increasingly important epigenetic biomarkers. These small (18–24 nucleotides (nts)), single-stranded, noncoding RNAs play critical roles in a variety of cellular processes, including apoptosis, cell cycle, proliferation, differentiation, and angiogenesis, by simultaneously regulating the expression levels of several genes.…”
mentioning
confidence: 99%
“…Many studies in CRC have revealed that miRNAs may function as oncogenes or tumor suppressors and play a key role in tumorigenesis, and their markedly changing expression profiles between normal and tumor tissues may be associated with metastatic processes and drug resistance. The miRNAs thus continue to gain prominence as biomarkers with great diagnostic, prognostic, and therapeutic potential. ,, …”
mentioning
confidence: 99%
See 2 more Smart Citations